The digital transformation of the information professions: Exploring the impact of digital publishing and open access - Hawamdeh, Suliman; Alemeneh, Daniel; Allen, Jeff (Information Research an international electronic journal, 2025)
Introduction. The information professions encompass a range of interconnected disciplines that contribute to the effective creation, processing, management, dissemination, and preservation of information and knowledge in diverse formats and contexts. Major technological innovations of the 20th century, combined with the rise of open access, open educational resources, and digital publishing, have greatly impacted public engagement with information and changed how people learn, communicate, and participate in civic society. This paper examines the impact of open access and digital publishing on information science education and the broader digital transformation of the information professions. Method. The study adopts a historical and thematic analysis of major technological innovations and the emergence of open access (OA), Open Educational Resources (OER) and digital publishing platforms, focusing on pioneering initiatives in the information science field such as Information Research, First Monday, and the Journal of Digital Information (JoDI). Results. Early open access and digital publishing pioneering initiatives served as catalysts for democratizing information access and reshaping the information field professional identities. Open access dismantled traditional barriers, facilitating global participation and promoting pedagogical innovation and resource sharing. Conclusion. The study highlights the pivotal role of open access and digital publishing in the digital transformation of the information profession. It underscores the ongoing evolution of the information professions by positioning information professionals at the forefront of a global movement for equitable access to information and knowledge.